The MicroArcsecond Scintillation-Induced Variability (MASIV) Survey: Detection of Angular Broadening at High Redshift? - Pursimo, T.; Ojha, R.; Jauncey, J.; Lovell, J.; Dutka, M.; Bignall, Hayley; Macquart, Jean-Pierre; rickett, B.; Kedziora-Chudczer, L. (Astronomical Society of the Pacific, 2008)
Interstellar scintillation has been shown to be primarily responsible for intra-day variability exhibited by extragalactic sources at centimeter wavelengths. The recent MASIV survey has shown that a very high proportion of flat spectrum extragalactic radio sources scintillate; such behaviour is both too common and too important to ignore. A study of the physical properties of the MASIV objects is severely handicapped by the absence of reliable redshift measurements for most of the objects. We present the first results of the studies of the physical properties of the MASIV sources, based on archival and our own redshift measurements.